Les effets biologiques de l’extrait de la Maclura Pomifera - CHALAKH, HAFIDA; LIMAM, MERIEM (My University, 2018)
The present study investigates the determination of anti-oxidant, antimicrobial and antiinflammatory properties of phenolic extracts of Maclura Pomifera. The antioxidant activity was evaluated with the following tests: DPPH (2,2-Diphenyl-1-picrylhydrazyl), and FRAP (Ferric Ion Reducing Antioxidant Power). Spectrophotometric quantification of total polyphenols by the Folin-Ciocalteu method and total flavonoids by the AlCl3 method gave higher values with the Ethyl Acetate Extract compared with the methanolic extract. The important antioxidant activities were significantly correlated with the total content of phenolic compounds. The antimicrobial activity was evaluated by the method of agar wells against different pathogenic strains, the results obtained revealed a varied antibacterial activity from one strain to another and also depends on the concentration of the tested sample. We evaluated the anti-inflammatory activity by testing, in vitro, the resistance of human red blood cells pretreated with the Osage fruit extract, and by the invivo inhibition test for edema. from the right hind paw of rats to carrageenan. We consider that the observations made in vitro and invivo are only a first stage of research for the evaluation of the biological properties of the bioactive substances of Maclura Pomifera.
Keywords: Maclura Pomifera; Antioxidant activity; Phenolic extracts; anti-inflammatory activity; antimicrobial activity.; Activité antioxydante; Extraits phénoliques; activité antiinflammatoire; activité antimicrobienne